Factors influencing online travel service satisfaction among Public University students in Kelantan - Najwa Ibrahim; Naziraazima Mahiruddin; New Yen Sin; Mohd Najmi Md Khatib (2016)
The purpose of this study is to determine the factors that influence online travel service satisfaction among public university students in Kelantan. Several factors that influence online travel service satisfaction which is website design, trust, information quality and also responsiveness. This research was conducted' by used descriptive and correlation research design which used questionnaire to identify the factor that influences online travel service satisfaction among public university student in Kelantan. Additionally, three public university students in Kelantan were selected which is UMK, UiTM and also USM. This research used approach of quantitative for data collection method. The findings of the content analysis provide evidence to suggest that online travel companies are underperforming in terms of providing web service quality attributes that enhance customer satisfaction. The findings from the content analysis also stated that online travel service satisfaction was influence by website design, trust, information quality and responsiveness. This study finding contributes to the present body of knowledge and also highlights web site quality dimensions that customers utilize in their assessment of overall online satisfaction. Moreover, this study also can contributes to future researchers which is they can choose more or other independent variable. Overall, public university students in Kelantan are satisfied with the online travel services offered.